0317 Molecular breeding values distribution in slick male and female Senepol cattle differing in musculature. (1st October 2016) - González-Berríos, C. L.; Rivera-Serrano, A.; Casas-Guérnica, A.; Sonstegard, T.; Pagán-Morales, M.
Abstract: Recently, the polymorphisms responsible for double muscling [MSTN: exon 3 11bp indel (NT821)] and slick coat phenotype (PRLR: exon 10 cytosine indel) in Senepol cattle were described. However, the genomic implications of segregating animals according to PRLR and MSTN genotypes have not been elucidated for economically relevant traits (ERTs), especially in tropically adapted beef cattle. Thus, purebred Senepol cattle (males/females) were genotyped for both indel and molecular breeding values (MBV) were obtained through a commercially available marker panel (Igenity, Neogen Corp.). Three MBV categories were established: low (L), intermediate (I) and high (H) based on standard deviations of +1 (L), +2 (I) or +3 (H) from the average MBV for 12 ERTs. Statistical differences were determined using the Chi 2 test [sex, genotype (MSTN; PRLR) and double and triple combinations]. Genotypic proportions observed were: double muscle (DM): 6/NT821-NT821, 95/NT821-WT, and normal musculature (NM): 273 WT-WT ( P < 0.0001) and slick coat (SC): 256/BB, 99/BA, and normal coat (NC): 4 = AA ( P < 0.0001). Proportional differences were observed within BB for MBV-average daily gain between MSTN genotypes: NT821/WT: (11.76 H, 72.06 I, 16.18 L) and NM: (26.06 H, 53.72 I, 20.21 L) ( P < 0.05). Also, within BB, differences in MBV categories distribution were: males: (20.90 H, 79.10 I, 0.00 L)/females: (33.33 H, 56.08 I, 10.58 L) and females: (16.93 H, 68.78 I, 14.29 L)/males: (4.48 H, 77.61 I, 17.91 L) for average daily gain and calving ease, respectively ( P < 0.05). Significant differences in MBV-tenderness were observed within females for: NT821/WT (7.46% H, 68.66% I, 23.88% L) and NM: (14.22% H, 73.04% I, 12.75% L) ( P < 0.05). Moreover, females BB ( n = 189) significantly differed in MBV category distribution depending on musculature for: residual feed intake [NT821/WT: (26.83 H, 68.29 I, 4.88 L)/NM: (18.92 H, 60.14 I, 20.95 L), yield grade [NT821/WT: (24.39 H, 70.73 I, 4.88 L)/NM: (14.19 H, 66.89 I, 18.92 L)], backfat thickness [NT821/WT: (57.14 H, 38.10 I, 4.76 L)/NM: (27.70 H, 50.0 I, 22.30 L)], pregnancy rate [NT821/WT: (4.88 H, 78.05 I, 17.07 L)/NM:(25.00 H, 66.22 I, 8.78 L)] and Stayability [NT821/WT: (9.76 H, 63.41 I, 26.83 L)/NM: (18.24 H, 70.27 I, 11.49 L)] ( P < 0.05). In the present study, a higher proportion of Senepol cattle with SC and NM were observed and intermediate MBV for all ERTs were predominant, with the exception of backfat thickness (NT821/WT-BB-Females). Therefore, genomic selection in slick Senepols segregating MSTN alleles are needed to improve their ERTs-MBV.